2010
DOI: 10.4103/0019-5278.75692
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, melatonin level, and sleep insufficiency among electronic equipment repairers

Abstract: Background:Exposure to extremely low frequency electromagnetic field (ELF-EMF), especially among electronic equipment repairers may induce oxidative stress and affect sleep quality.Aims:This study was carried out to (a) investigate the effect of exposure to ELF-EMF on the malondialdehyde (MDA) levels among electronic equipment repairers as an indicator of oxidative stress; and melatonin hormone levels; and (b) to study the prevalence of sleep insufficiency among electronic equipment repairers exposed to ELF-EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 21 publications
(29 reference statements)
0
19
0
1
Order By: Relevance
“…These ROS promote the formation of MDA, a lipid peroxidation end product in the kidney. The content of MDA is a good index of increased oxidative stress in the tissues, displaying raised peroxidation processes [37]. Also, they distort the normal functioning of antioxidant enzyme cascade such as SOD, catalase and GSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ROS promote the formation of MDA, a lipid peroxidation end product in the kidney. The content of MDA is a good index of increased oxidative stress in the tissues, displaying raised peroxidation processes [37]. Also, they distort the normal functioning of antioxidant enzyme cascade such as SOD, catalase and GSH.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that 5 day pre-treatment with NDGA, along with cisplatin, significantly decreased the levels of BUN and creatinine, indicating the protective effect of NDGA against cisplatin induced nephrotoxicity. MDA is a degradation product of lipid hydroperoxide, which provides an index of the peroxidation of lipids in body tissue [37]. It is well known that cisplatin causes lipid peroxidation in the kidney by generating reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini menunjukkan terdapat hubungan kejadian kurang tidur dengan keterpaparan gelombang elektromagnetik yang tinggi. 8 Anak dan remaja yang mempunyai durasi tidur cukup mengonsumsi media seperti menonton televisi (TV) dan menggunakan komputer yang rendah. 9 Sekitar 72% penduduk Asia cenderung menggunakan internet sebelum tidur dibanding etnik yang lain.…”
Section: Pendahuluanunclassified
“…As elevated levels of oxidative stress were associated with AD, it is also important to stress that EMF effects on oxidative stress have also been reported in numerous investigations (e.g. Wolf et al ., ; Akdag et al ., ; El‐Helaly and Abu‐Hashem, ; Goraca et al ., ; Emre et al ., ). It was also found that treatment of rats with melatonin and the spin‐trap compound N‐tert ‐butyl‐ α ‐phenylnitrone could block the effect of magnetic fields on brain cell DNA, suggesting that free radicals may play a role in magnetic‐field‐induced DNA damage (Lai and Singh, ).…”
Section: Different Pathways To Explain the Possibility Of An Increasementioning
confidence: 99%